PSYCHOLOGICAL STATE OF UKRAINIAN MILITARY PERSONNEL: THE EFFECTIVENESS OF PSYCHOLOGICAL ASSISTANCE AND THE NEED FOR FURTHER PSYCHOLOGICAL SUPPORT (Psychology Travelogs, 2025)
The articlepresents the results of a study of the psycho-emotional state of military personneland veterans who participated in the defense of Ukraine since the beginning of the full-scaleinvasion by the Russian Federation. Changes in physical, emotional, behavioral, andcognitive spheres are analyzed based on data obtained during the implementation of the statepsychological rehabilitation program coordinated by the Ministry of Veterans Affairsof Ukraine. The empirical basis for the study was the Psychological Support Cardsfor recipients of psychological assistance services, approvedby Order No. 331 of the Ministry of Veterans Affairs on December 14, 2023. The paper examines in detail the symptoms, their dynamics, and the most common requests from veterans. The analysis was conducted in four areas: physical manifestations, emotional manifestations, as well as behavioral and cognitive manifestations, which allows covering all aspects of human well-being. Based on the results of the correlation analysis, the interrelationships between the most common manifestations characterizing the psychological state of military personnel were determined. The results of a qualitative analysis are presented – a comparison of data on military personnel in 2022 before receiving psychological assistance and in 2025. The results show a deterioration in almost all of the selected indicators—compared to the beginning of the war, there has been a significant increase in tension, fatigue, burnout, chronic stress, etc., which requires special attention from psychologists and targeted work to ensure combat readiness. The transition to civilian life for military personnel (“discharge”) does not eliminate, but rather exacerbates, the characteristics that the war has brought to their psyche, requiring special attention and psychological support.There is a significant need to strengthen the neuromedical component of care and introduce modern rehabilitation protocols. A number of practical recommendations have been proposed to improve state policy in the field of mental health for military personnel.
Keywords: psychological assistance; psychological rehabilitation; combatants; combat experience; psychological state; neurorehabilitation